Aspergillus waksmanii sp. nov. and Aspergillus marvanovae sp. nov., two closely related species in section Fumigati - Hubka, Vit; Peterson, Stephen W; Frisvad, Jens C; Yaguchi, Takashi; Kubátová, Alena; Kolařík, Miroslav (International journal of systematic and evolutionary microbiology, 2013)
Two new and phylogenetically closely related species in Aspergillus section Fumigati are described and illustrated. Homothallic Aspergillus waksmanii sp. nov. was isolated from New Jersey soil (USA) and is represented by the ex-type isolate NRRL 179(T) ( = CCF 4266(T) = Thom 4138.HS2(T) = IBT 31900(T)). Aspergillus marvanovae sp. nov. was isolated from water with high boracic acid anions content in Dukovany nuclear power station (Czech Republic). The sexual stage of this species is unknown, but the MAT1-1 locus was successfully amplified suggesting that the species is probably heterothallic and teleomorphic but is represented by only the ex-type isolate CCM 8003(T) ( = CCF 4037(T) = NRRL 62486(T) = IBT 31279(T) = IFM 60873(T)). Both species can be distinguished from all previously described species in section Fumigati based on morphology, maximum growth temperature, sequence data from five unlinked loci and unique secondary metabolites profiles.
Keywords: New Jersey; DNA, Fungal; fylogeneze; mykologické určovací techniky; Genes, Mating Type, Fungal; Česká republika; Aspergillus; Phylogeny; Sequence Analysis, DNA; sekvenční analýza DNA; molekulární sekvence - údaje; Soil Microbiology; mezerníky ribozomální DNA; DNA fungální; Czech Republic; Mycological Typing Techniques; půdní mikrobiologie; DNA, Ribosomal Spacer; Molecular Sequence Data; fungální geny pro párovací typ